2011
DOI: 10.11130/jei.2011.26.3.554
|View full text |Cite
|
Sign up to set email alerts
|

FDI and Economic Growth: Causality for the EU and ASEAN

Abstract: This study attempts to address the causal-order between inward FDI and economic growth using a panel data set for two different Economic Associations that is EU (European Union) and ASEAN (Association of South Eastern Asian Nations) over the period 1970-2003. The inflows of FDI to developed host countries raise the question of how these inflows affect their economies and what is the interaction between FDI and growth. While there is considerable evidence on the link between FDI and Economic Growth , the causal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 48 publications
2
15
0
1
Order By: Relevance
“…Long-run causality, on the other hand, is tested through the lagged co-integrating vectors ‫ܶܥܧ‬ ଵ,௧ିଵ and ‫ܶܥܧ‬ ଶ,௧ିଵ (Ghali, 1998;Zhang, 2001;Fowowe, 2011;and Moudatsou & Kyrkilis, 2011 According to Granger (1986Granger ( , 1988b and Ghali (1998), if two variables are cointegrated, then: (i) the VECM framework should be employed; and (ii) Granger causality must exist in at least one direction. Engle and Granger (1987) showed that if two non-stationary variables are cointegrated, a VAR in the first difference could be misspecified.…”
Section: Vector Error Correction Model (Vecm)mentioning
confidence: 99%
“…Long-run causality, on the other hand, is tested through the lagged co-integrating vectors ‫ܶܥܧ‬ ଵ,௧ିଵ and ‫ܶܥܧ‬ ଶ,௧ିଵ (Ghali, 1998;Zhang, 2001;Fowowe, 2011;and Moudatsou & Kyrkilis, 2011 According to Granger (1986Granger ( , 1988b and Ghali (1998), if two variables are cointegrated, then: (i) the VECM framework should be employed; and (ii) Granger causality must exist in at least one direction. Engle and Granger (1987) showed that if two non-stationary variables are cointegrated, a VAR in the first difference could be misspecified.…”
Section: Vector Error Correction Model (Vecm)mentioning
confidence: 99%
“…More specifically, the empirical evidence points out that in Southeast Asian countries FDI contributes significantly to GDP growth (Bhatt, 2014;Moudatsou & Kyrkilis, 2011;Choong & Liew, 2009). Additionally, studies in which trade-related measures and FDI are included simultaneously to investigate long-run growth eff ects, reveal the presence of intricate interrelationships (Sothan, 2016;Tan & Tang, 2016;Bhatt, 2014).…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
“…Before proceeding for the Cointegration test, the econometric methodology says all the suggested variables in the model must be integrated in order I(1). Fowowe (2011) described that after testing the unit root there are two ways of testing the causality (i) the first condition is that when the variables are integrated in order I(1) and Cointegrated then the VECM is the best choice to be used, see also (Emirmahmutoglu & Kose, 2011;Fowowe, 2011;Moudatsou & Kyrkilis, 2011;Zhang, 2001) the (ii) way is that if the proposed variables are not integrated in the same order then the causality should be proceed by the VAR approach, see also (Fowowe, 2011;Toda & Phillips, 1993). But before going to the empirical analysis of a detailed summary of the proposed variables in Table 1.…”
Section: Data and Estimation Strategymentioning
confidence: 99%